2013
DOI: 10.1186/2040-7378-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of FTY720 and rt-PA in an experimental model of large hemispheric stroke–no influence on functional outcome and blood–brain barrier disruption

Abstract: BackgroundSystemic thrombolysis with recombinant tissue plasminogen activator (rt-PA) is the standard of acute stroke care. Its potential to increase the risk of secondary intracerebral hemorrhage, especially if administered late, has been ascribed to its proteolytic activity that has detrimental effects on blood–brain barrier (BBB) integrity after stroke. FTY720 has been shown to protect endothelial barriers in several disease models such as endotoxin-induced pulmonary edema and therefore is a promising candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…FTY720 treatment in pMCAO did not affect stroke outcome, findings that might suggest that any beneficial effect is through mechanisms exclusive to R/I ( 228 , 229 ). Yet another study failed to show any benefit when fingolimod was given in combination with rt-PA, thus contradicting the results of the above referenced investigation ( 245 ).…”
Section: Anti-inflammatory Treatmentsmentioning
confidence: 89%
“…FTY720 treatment in pMCAO did not affect stroke outcome, findings that might suggest that any beneficial effect is through mechanisms exclusive to R/I ( 228 , 229 ). Yet another study failed to show any benefit when fingolimod was given in combination with rt-PA, thus contradicting the results of the above referenced investigation ( 245 ).…”
Section: Anti-inflammatory Treatmentsmentioning
confidence: 89%
“…Our data suggest a new mechanism by which FTY720 protects against ischemic insults, in which FTY720 preserves the BBB tight and adherens junction on the cell lamellipodia and prevents them from redistributing to the cytoplasm. In contrast, there have been conflicting reports, suggesting that co-administration of FTY720 and recombinant tissue plasminogen activator (rt-PA) can exacerbate BBB disruption [36], or that TEER of endothelial cells exposed to IFNγ and TNFα were not changed by FTY720-P administration [37]. Reports from Hla et al also showed that FTY720 facilitates selective BBB permeability to small molecules under physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological function was evaluated directly prior to the stroke surgery and at 24 h post-MCAO before the second MRI on a 14 point scale neuroscore mNSS modified by Cai et al . 39 , testing hemiparesis, gait, coordination and sensory functions.…”
Section: Methodsmentioning
confidence: 99%